Penentuan Jumlah dan Efisiensi Tenaga Kerja Pengemasan Dengan Metode Work Sampling - Andrew Setiawan Rusdianto; Liesia Hanagari; Bambang Herry Purnomo; Ida Bagus Suryaningrat; Yuli Wibowo (JOFE : Journal of Food Engineering, 2022)
Determination of the number of workers is one step to increase efficiency and productivity. Packaging has an important role to increase productivity. The purpose of the work measurement is to determine the standard time with the work sampling method so that it can be seen the number of workers needed. Observation of 2 trained workers for 10 days with 30 observations per day. The results showed that the average productive percentage in shift 1 of labor 1 was 96% and labor 2 was 93%. While in the second shift 2 workers have a productive percentage of 92%. The standard time in shift 1 is 1,2946 minutes/unit with a load of 233.28% and 1,3009 minutes/unit for a workforce with a load of 263.55%, while in shift 2, the workforce 1 is 1.3038. minutes/unit with a load of 320.16% and a workforce of 1.3401 minutes/unit with a load of 346.84%. Based on the calculation of the efficiency of shift 1 workers with efficient achievements of 95.00% and 86.67%. Likewise, with the efficiency of shift 2 workers with efficient achievements of 88.33% and 86.00%. So the number of workers needed is 5 people/machine.